Collaboration Is the Key – The Role of Special Educators in Inclusive Schools in Germany - Neumann, Phillip; Lütje-Klose, Birgit (International Perspectives on Inclusive Education)
Inclusive education is about creating beneficial environments for all students (Booth & Ainscow, 2011). Within Germany, the role of special education within inclusive schools has been widely discussed in Germany (Powell et al., 2016). Educators worldwide consider collaborative teaching between special educators and general educators to be a fundamental precondition for inclusive education (Hoppey & McLeskey, 2014). The history of the German school system, however, is characterized by a rigorous division of special and regular schools that is reflective of broad divisions in teacher education. Since the ratification of the Convention on the Rights of Persons with Disabilities (CRPD) in Germany in 2009, more students with special educational needs, as well as special educators, have begun to attend and work in inclusive schools. While cooperation between general and special educators is a key to the development of inclusive schools, many teachers report that responsibilities are divided between special and general teachers, while various challenges exist regarding cooperation (Urban & Lütje-Klose, 2014). Nevertheless, dysfunctional cooperation can foster mechanisms of separation and exclusion even in “inclusive” settings (Idel et al., 2019). The present chapter offers a reflection on the different roles of special educators and the current state of research on interdisciplinary and multi professional cooperation in inclusive schools in Germany. It also provides a discussion of relevant implications for the development of inclusive schools and teacher training.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; Inclusion; Cooperation; Collaboration; Team-Teaching; International; Germany

Together Strong: Cooperative Android App Analysis - Pauck, Felix; Wehrheim, Heike (Proceedings of the 2019 27th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering)
Recent years have seen the development of numerous tools for the analysis of taint flows in Android apps. Taint analyses aim at detecting data leaks, accidentally or by purpose programmed into apps. Often, such tools specialize in the treatment of specific features impeding precise taint analysis (like reflection or inter-app communication). This multitude of tools, their specific applicability and their various combination options complicate the selection of a tool (or multiple tools) when faced with an analysis instance, even for knowledgeable users, and hence hinders the successful adoption of taint analyses. In this work, we thus present CoDiDroid, a framework for cooperative Android app analysis. CoDiDroid (1) allows users to ask questions about flows in apps in varying degrees of detail, (2) automatically generates subtasks for answering such questions, (3) distributes tasks onto analysis tools (currently DroidRA, FlowDroid, HornDroid, IC3 and two novel tools) and (4) at the end merges tool answers on subtasks into an overall answer. Thereby, users are freed from having to learn about the use and functionality of all these tools while still being able to leverage their capabilities. Moreover, we experimentally show that cooperation among tools pays off with respect to effectiveness, precision and scalability.
Keywords: Android Taint Analysis; Cooperation; Precision; Tools

Kollaboration und Kooperation beim Klassenmusizieren mit Populärer Musik. Musikmachen in der Schule im Spannungsfeld von Lernen mit der Gruppe und für die Gruppe - Godau, Marc (Soziale Aspekte des Musiklernens)
Within recent years, research on music learning in groups has increased. But the distinction between collaboration and cooperation is mostly unclear. This article aims to distinguish both concepts by presenting a study on popular music learning in groups (Godau, 2017) based on elements of the learning approach in Musical Futures (Green, 2008). As a result, the two concepts are seen as complementary. They form the poles of a continuum of collective learning: Collaboration characterizes the collective action toward the common goal. By contrast, cooperation occurs when group members act separately toward achieving the common goal. (DIPF/Orig.)
Keywords: Kollaboration; Musik; Learning; Lernen; Musical education; Musikpädagogik; Pop music; Popmusik; Popular Music; Studie; Musikunterricht; Music lessons; Qualitative Forschung; Qualitative research; Teaching of music; Constructivism; Cooperation; Cooperative learning; Gruppe; Klassenmusizieren; Konstruktivismus; Kooperation; Kooperatives Lernen; Learning psychology; Lernpsychologie; Psychology of learning

Encouraging Family and Parent Education: Program Development and Evaluation in the Federal State of Baden-Württemberg, Germany - Landhäußer, Sandra; Faas, Stefan; Treptow, Rainer (Center for Educational Policy Studies Journal (CEPS))
Against the background of a European-wide strategy of governance aimed at improving support for parents and families, the following report details the conceptualization and evaluation of a federal state program4 in Baden- Württemberg (Germany) which was launched in 2008 to encourage fam- ily and parent education. Two program components, a voucher system for parents with a new-born child and an element that emphasizes educa- tional offers for families with special needs in particular living situations, were started to increase requests for educational courses. The aim was to establish and deepen cooperation between different public and private professional services that are in contact with parents and their children. The results show that main goals of the program were reached.
Keywords: family and parent education; cooperation; voucher system; support for families with special needs in particular living situations; program evaluation